Integrating enzyme-nanoparticles bring new prospects for the diagnosis and treatment of immune dysregulation in periodontitis - Zhang, Qianqian; Wang, Zhiyi; Shen, Shijiao; Wang, Junzhe; Cao, Jun; Deng, Yongqiang; Meng, He; Ma, Lin (Frontiers in Cellular and Infection Microbiology, 2024)
Enzymes play a significant role in mediating inflammatory and immune responses in periodontitis. Effective diagnosis, timely treatment, and continuous management of periodontal enzymes are essential to prevent undesirable consequences; however, this remains a significant challenge. Nanoparticles (NPs) have attracted significant attention in biomedicine because of their advantageous nanosized effects. NPs are conjugated with specific enzyme substrates at responsive sites that are triggered by periodontitis enzyme biomarkers, leading to functional or characteristic changes. In contrast, NPs with enzyme-mimetic activities exhibit catalytic activity, effectively destroying pathogenic biofilms and modulating the immune response in periodontitis. The unique properties of enzyme-targeting NPs have enabled the development of biosensors and fluorescent probes capable of identifying enzyme biomarkers associated with periodontitis. Enzyme-responsive and enzyme-mimetic NPs both exert therapeutic applications in the treatment of periodontitis. In this review, we provide a comprehensive overview of the enzymes associated with periodontitis, the mechanisms of enzyme-responsive and enzyme-mimetic NPs, recent advancements in the use of NPs for detecting these enzymes, and the therapeutic applications of NPs in targeting or mimicking enzyme functions. We also discuss the challenges and prospects of using NPs in the diagnosis and treatment of periodontitis.